2022
DOI: 10.3390/plants11202670
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Wild Food Plant Use Diversity in the Soviet Union, 1922–1991

Abstract: In the Soviet Union, wild food played a secondary role in diet (as cultivated species dominated). Yet the authorities eventually acknowledged their importance as diet diversifiers and a safety reservoir, and started to promote their use through various means, including publishing books on the use of wild food plants. These government publications appeared during a specific time, and therefore, we mapped all centralized publications in order to understand the dynamics of the promotion of wild-plant-related know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In a study conducted in Russia on wild dietary plants, Sorbus aucuparia had the most numerous proposed dietary usages, followed by Rosa canina L. and Vaccinium oxycoccos L. [ 15 ].…”
Section: History and Originsmentioning
confidence: 99%
“…In a study conducted in Russia on wild dietary plants, Sorbus aucuparia had the most numerous proposed dietary usages, followed by Rosa canina L. and Vaccinium oxycoccos L. [ 15 ].…”
Section: History and Originsmentioning
confidence: 99%
“…By studying historical ethnobotanical literature from the interwar period, it is clear that many communities from the Republic of Moldova (at that time called Bessarabia and was a part of the Romanian Kingdom) had incredibly rich ethnobotanical knowledge and very elaborate receipes for the preparation of medicinal teas to treat different illnesses. When such cases are encountered, it is mandatory that the researcher try to identify the influence of external sources in local intergenerationally transmitted knowledge, especially when the rest of the community considers certain persons as local experts (see Bexultanova et al 2022, Mattalia et al 2020). The existence of local experts specialized in medicinal plants with external knowledge sources (books, magazines) is a recent reality in (south-eastern) European rural communities, but researchers should not underestimate the traditions of peasant herbalists that might still exist in some European regions.…”
Section: Impact By External Sources Of Plant Knowledge In Southeast E...mentioning
confidence: 99%
“…Furthermore, two articles analyze plant availability instead of interviewing people [53][54][55], while some others analyze historical sources and literature to assess wild plant use [51,[55][56][57][58][59][60][61]. As for the characteristics of the studied territory, most of the selected articles focused on a well-defined rural area, again with some exceptions: some focused on urban areas [53,[62][63][64] or food markets [44,46,47], while others analyzed more generally different areas of a country [43,44,47,49,50,52,58,59,61,[65][66][67][68]. The articles selected for the systematic review, together with the aforementioned features and the specific area of study, are listed in Appendix A.…”
Section: Descriptive Statistics On Selected Papersmentioning
confidence: 99%
“…Policies and national support for businesses can influence the extent of foraging practices [85]. Some authors reported that state-induced procurement has historically played a role in keeping foraging practices alive [51,68,132]. As it will be further discussed in the next session, centralized procurement could lead to misleading results.…”
Section: Other Influencesmentioning
confidence: 99%